2021
DOI: 10.3390/nu13093174
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean Diet, Alcohol Consumption and Emotional Eating in Spanish University Students

Abstract: (1) Introduction: The university period may increase the risk of different unhealthy habits, such as low adherence to the Mediterranean diet, high alcohol consumption and eating in response to specific emotions. The aim of this study was to detect early-risk alcohol consumption and alcohol dependence (ADS), the degree of adherence to the Mediterranean diet and emotional eating in university students of the Madrid community. (2) Methods: For each individual, anthropometric parameters, the Alcohol Use Disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 68 publications
5
23
2
1
Order By: Relevance
“…In Spain, the majority of people follow a Mediterranean diet, which is a healthy diet [7]. Previous research has revealed that the low adherence of Spanish university students to a Mediterranean diet is related to high alcohol consumption [5,8], smoking, low levels of physical activity (PA), living alone, and leading a sedentary lifestyle [5], and good adherence to the Mediterranean diet is associated with an improved quality of life related to perceived health [9] and low body weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, the majority of people follow a Mediterranean diet, which is a healthy diet [7]. Previous research has revealed that the low adherence of Spanish university students to a Mediterranean diet is related to high alcohol consumption [5,8], smoking, low levels of physical activity (PA), living alone, and leading a sedentary lifestyle [5], and good adherence to the Mediterranean diet is associated with an improved quality of life related to perceived health [9] and low body weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, 15.5% of Italians and 30.7% of Spaniards showed hazardous alcohol use. A recent study conducted in Spain reported that 26.2% of participants were categorized as high-risk drinkers, according to the AUDIT questionnaire [ 15 ]. Carlos et al [ 14 ] found that 17.6% of the recruited Spanish university students may be considered at risk of developing alcohol dependency, and 2.4% can be considered as having alcohol dependence syndrome (ADS).…”
Section: Discussionmentioning
confidence: 99%
“…Carlos et al [ 14 ] found that 17.6% of the recruited Spanish university students may be considered at risk of developing alcohol dependency, and 2.4% can be considered as having alcohol dependence syndrome (ADS). López-Moreno et al [ 15 ], according to the AUDIT score, categorized 26.2% of Spanish university students as high-risk drinkers, and 7.7% as suffering from ADS [ 15 ]. In our study, the safe consumption of alcohol can be due to the habits of our sample, since 77.4% of Italians and 73.0% of Spaniards stated to generally stay at home in the evening, while 22.6% of Italians and 27.0% of Spaniards went out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations